ABOUT THE SPECTROPHOTOMETRICAL STANDARDS IN THE ULTRVIOLET REGION OF SPECTRA - Tereschenko, V.M. (Recent Contributions to Physics, 2011)
The problems of the standardization of observations of celestial bodies in ultraviolet region are discussed. We propose extension the list of the prime spectrophotometrical standards in far UV-region by the 7 B-A-stars of main sequence.